2014
DOI: 10.1186/1750-9378-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and delay of diagnosis among Kaposi’s sarcoma patients in Uganda: a cross-sectional study

Abstract: BackgroundIn low- and middle-income countries, the association between delay to treatment and prognosis for Kaposi’s sarcoma (KS) patients is yet to be studied.MethodsThis is a prospective study of HIV-infected adults with histologically-confirmed KS treated at the Uganda Cancer Institute (UCI). Standardized interviews were conducted in English or Luganda. Medical records were abstracted for KS stage at admission to UCI. Multivariable logistic regression assessed relationships between diagnostic delay and stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Starting use of T&CM before seeking care at biomedical facilities potentially delays health seeking. Other studies have shown that patients with cancer who take recourse to T&CM often delay by several months to be diagnosed and are often in advanced stage disease at presentation (Broom et al, ; De Boer, Niyonzima, Orem, Bartlett, & Zafar, ; Kerdpon & Sriplung, ; Maghous et al, ). These findings have important implications for interventions to promote early detection of cancers by targeting the THPs who are visited earlier on in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Starting use of T&CM before seeking care at biomedical facilities potentially delays health seeking. Other studies have shown that patients with cancer who take recourse to T&CM often delay by several months to be diagnosed and are often in advanced stage disease at presentation (Broom et al, ; De Boer, Niyonzima, Orem, Bartlett, & Zafar, ; Kerdpon & Sriplung, ; Maghous et al, ). These findings have important implications for interventions to promote early detection of cancers by targeting the THPs who are visited earlier on in the disease trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a healthcare-facility-based randomized trial of an intervention to improve early detection of KS failed to improve outcomes in Zimbabwe 173 . The use of traditional healers by patients with KS in resource-limited settings may also delay early detection 174 . Thus, it is likely that the bene- fits of early KS detection will be realized only through community-based public education campaigns.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Cutaneous lesions may also disfigure and lead to social stigma for KS patients [ 5 , 6 ]. The prognosis of KS patients in sub-Sahara Africa is generally poor, often due to delayed diagnosis and late initiation of treatment [ 7 ]. Even after receiving anti-retroviral drugs therapy (ART), the mortality of epidemic KS patient is often high due to advanced KS disease staging, simultaneous advanced HIV-1 diagnosis and both HIV-1 and KS-immune reconstitution inflammatory syndromes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%